Environmental Flows in Water Resources Policies, Plans, and Projects : Findings and Recommendations - Hirji, Rafik; Davis, Richard (World Bank, 2012)
The overall goal of the analysis presented in this report is to advance the understanding and integration in operational terms of environmental water allocation into integrated water resources management. The specific objectives of this report are the following: 1) document the changing understanding of environmental flows, by both water resources practitioners and by environmental experts within the Bank and in borrowing countries; 2) draw lessons from experience in implementing environmental flows by the Bank, other international development organizations with experience in this area, and a small number of developed and developing countries; 3) develop an analytical framework to support more effective integration of environmental flow considerations for informing and guiding: (a) the planning, design, and operations decision making of water resources infrastructure projects; (b) the legal, policy, institutional, and capacity development related to environmental flows; and (c) restoration programs; and 4) provide recommendations for improvements in technical guidance to better incorporate environmental flow considerations into the preparation and implementation of lending operations.